Political participation : a comparative sudy of undergraduate students in the Departments of Political Science and English Language and Literature - Harahap, Ali Musa (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
Political participation is one of the indicators of democracy. This study examines the political participation of final year undergraduate students of Department of Political Science and Department of English Language and Literature at the International Islamic University Malaysia. The main objective of this study was to analyse the level of students' political involvement in both departments. It also examines the factors that influence students' political participation. The population of this study was the final year Political Science and English Language and Literature students from the Kulliyyah of Islamic Revealed Knowledge and Human Sciences. This study adopts a quantitative approach in data collection through the instrument of questionnaire. This study finds that the respondents' political participation is average. However, in terms of percentage, the results show that PSCI students are more politically engaged than BENL students. This study also finds that Political Consciousness and Political Socialisation have positive relationship to students' political participation.